Web-Based Information Services in Selected Academic Libraries, Nigeria - Chioma Augusta Ezeabasili; Prisca Iheoma Nwachukwu; Ogagaoghene Uzezi Idhalama (Researchparks Publishing, 2022)
This work investigated the web-based information services in selected academic libraries, Nigeria. The descriptive survey research design was used for the study, as well as the total enumeration sampling technique. The study's data was gathered through the use of a questionnaire. Academic librarians from Ambrose Alli University Library in Ekpoma and John Harris Library at the University of Benin in Benin City, both in Edo State, comprise the study's population. The study's respondents are one hundred (100) selected academic librarians from Ambrose Alli University Library and John Harris Library. This research study's data analysis method was simple percentages presented in tables, mean and standard deviation. Findings revealed, among other things, that there are reasons for adopting web-based services in academic libraries. Furthermore, the findings revealed some of the challenges that academic libraries face when implementing web-based library services. It was suggested, among other things, that government and academic library parent institutions adequately fund the library so that it can subscribe to online databases and acquire appropriate software that promotes the adoption and use of web-based services. It was also suggested that the government adequately fund the library in order to enable the acquisition of necessary technological equipment and infrastructure. It was also suggested that library staff be open to new trends and embrace the use of new technologies for information service delivery in the library. Academic librarians must be open to new technological trends and embrace technological advancements.